Riparian tree diversity and water quality of Teunbaun spring Kupang regency - Semiun, Chatarina Gradict; Mamulak, Yulita Iryani; Pani, Emilianus (Jurnal Biologi Udayana, 2024)
Springs are water resources for human. One of the components that maintain the springs is the riparian tree. The study aims to identify the diversity of riparian tree species and water quality in Teunbaun (Sonaf) spring, Kupang district. Measurement of tree samples used the Quadrant Sampling Technique, while water quality measurements included physical, chemical, and microbiological (MPN) parameters. Collected tree and water quality data were analyzed to determine endemism status, species richness index (Dmg), Shannon-Wiener diversity index (H’), and gap analysis (conformity of water quality profile with water quality standards). The results showed that 16 species of riparian trees from 12 families were found. The species that are often found are from the Arecaceae family. The value of Dmg and H’ were classified as moderate. The results of the physical and chemical quality tests of water revealed that almost all parameters achieved the quality standards, except for COD, cadmium and nickel. Futhermore, the MPN value found did not achieve the quality standar..